2022
DOI: 10.3390/cancers14163929
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Age on Postoperative Short-Term and Long-Term Outcome after Pancreatic Resection of Pancreatic Ductal Adenocarcinoma

Abstract: (1) Purpose: to evaluate the impact of age on postoperative short-term and long-term outcomes in patients undergoing curative pancreatic resection for PDAC. (2) Methods: This retrospective single-center study comprised 213 patients who had undergone primary resection of PDAC from January 2000 to December 2018 at the University Hospital of Erlangen, Germany. Patients were stratified according the age into two groups: younger (≤70 years) and older (>70 years) patients. Postoperative outcome and long-term surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The corresponding concomitant diseases such as hypertension, cardiovascular and cerebrovascular comorbidities were also more common in our patient cohort with regular aspirin intake. Furthermore, in our cohort patients taking aspirin were found to be older than patients without ASS intake (cASS: 74 years vs. iASS: 70 years vs. no ASS: 67 years, p = 0.039) and age was revealed as independent prognostic survival factor in our analysis and the previous studies [36].…”
Section: Discussionsupporting
confidence: 64%
“…The corresponding concomitant diseases such as hypertension, cardiovascular and cerebrovascular comorbidities were also more common in our patient cohort with regular aspirin intake. Furthermore, in our cohort patients taking aspirin were found to be older than patients without ASS intake (cASS: 74 years vs. iASS: 70 years vs. no ASS: 67 years, p = 0.039) and age was revealed as independent prognostic survival factor in our analysis and the previous studies [36].…”
Section: Discussionsupporting
confidence: 64%
“…Hackner et al [56] Retrospective .004 Xu et al [57] was associated with a longer median survival (17.2 months; 95% confidence interval [CI], 16.1-19.0) compared with those who did not receive adjuvant chemotherapy (12.7 months; 95% CI, 11.8-13.6) in the elderly PDAC patients (80 years or older) and this association was consistent in propensity and subgroup analyses. [58] Besides, further multivariable analysis indicated receipt of adjuvant chemotherapy (hazard ratio [HR], 0.72; 95% CI, 0.65-0.79; P < .001) was associated with a decreased hazard of death in the elderly PDAC patients.…”
Section: Safety Feasibility and Effect Of Chemotherapy In Elderly Pda...mentioning
confidence: 82%
“…[55] However, Hackner et al pointed out that the median OS and disease-free survival (DFS) were significantly shorter in elderly PDAC patients receiving surgery, and age was a significant independent prognostic predictor for OS and DFS. [56] Xu et al consistently observed that elderly PDAC patients were associated with worse OS survival after radical resection. [57] All these researches were based on the retrospective and non-randomized study, selection bias and confounding factors inevitably interfered.…”
Section: Clinical Management In Elderly Pdac Patientsmentioning
confidence: 99%